Placenta‐on‐a‐Chip: In Vitro Study of Caffeine Transport across Placental Barrier Using Liquid Chromatography Mass Spectrometry - Rajeendra L. Pemathilaka; Jeremy D. Caplin; Saurabh S. Aykar; Reza Montazami; Nicole N. Hashemi (Global Challenges, 2019)
Abstract Due to the particular structure and functionality of the placenta, most current human placenta drug testing methods are limited to animal models, conventional cell testing, and cohort/controlled testing. Previous studies have produced inconsistent results due to physiological differences between humans and animals and limited availability of human and/or animal models for controlled testing. To overcome these challenges, a placenta‐on‐a‐chip system is developed for studying the exchange of substances to and from the placenta. Caffeine transport across the placental barrier is studied because caffeine is a xenobiotic widely consumed on a daily basis. Since a fetus does not carry the enzymes that inactivate caffeine, when it crosses a placental barrier, high caffeine intake may harm the fetus, so it is important to quantify the rate of caffeine transport across the placenta. In this study, a caffeine concentration of 0.25 mg mL−1 is introduced into the maternal channel, and the resulting changes are observed over a span of 7.5 h. A steady caffeine concentration of 0.1513 mg mL−1 is reached on the maternal side after 6.5 h, and a 0.0033 mg mL−1 concentration on the fetal side is achieved after 5 h.